Construction of self-supporting heterobimetallic phosphides for oxygen evolution reaction - Adjapong Linda Akua Agyapomaa; Chulong Jin; Qingqing Zhang; Xiaojun Zeng (Materials Today Catalysis)
Electrocatalysts with heterobimetallic active sites are considered to be effective geometries for electrocatalytic oxygen evolution reaction (OER). However, MOF-derived heterobimetallic phosphides are uncontrollable and the addition of traditional binders is complicated. Here, we designed an efficient defect-rich (NF/Ni2P-Fe2P@NC) heterostructure derived from NF/Fe-MOF, in which nickel foam (NF) provides a supporting role and Ni source to promote the formation of heterobimetallic phosphides (Ni2P, Fe2P). NF/Ni2P-Fe2P@NC inherits remarkable OER performance with ultralow overpotential of 123 mV at a current density of 10 mA cm−2 and Tafel slope of 51. 3 mV dec−1 in alkaline electrolyte. The experimental results unravel that the multi-components (Ni2P, Fe2P, NC), rich heterogeneous interfaces (Ni2P/Fe2P), and numerous defects in the heterostructure provide abundant active sites, optimize the electronic structure, and improve the exposure of active sites, thereby promoting the electrocatalytic OER process. Density functional theory (DFT) calculations confirm that the free energy barrier for the catalyst to generate *OOH intermediates is low. Our findings present a simple and economical approach to obtaining heterobimetallic phosphides with robust OER performance.